2012
DOI: 10.1111/j.2044-8260.2012.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of PTSD following recovery from first‐episode psychosis: The threat from persecutors, voices, and patienthood

Abstract: It may be that retrospective studies have overestimated the influence of candidate appraisals in predicting PTSD. It might also be that assessments made during the acute phase of psychosis preceded a key phase of psychological processing that takes place during the immediate aftermath of the psychotic episode. A staged prospective design is required to uncover the true impact of psychosis on PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 58 publications
1
42
1
Order By: Relevance
“…FEP participants were interviewed 3-6 months after their acute episode (Time 1) to ensure some resolution of the episode and 3-4 months after the first interview (Time 2). Three to six months after the acute episode is also considered early recovery (Early Psychosis Guidelines Writing Group, 2010) and a period of adjustment (Brunet, Birchwood, Upthegrove, Michail, & Ross, 2012). Significant others and clinicians were interviewed at Time 2 on average 7 days after FEP participants' interviews.…”
Section: Methodsmentioning
confidence: 99%
“…FEP participants were interviewed 3-6 months after their acute episode (Time 1) to ensure some resolution of the episode and 3-4 months after the first interview (Time 2). Three to six months after the acute episode is also considered early recovery (Early Psychosis Guidelines Writing Group, 2010) and a period of adjustment (Brunet, Birchwood, Upthegrove, Michail, & Ross, 2012). Significant others and clinicians were interviewed at Time 2 on average 7 days after FEP participants' interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Together, these data have posed the question of what variables could be modulating the relationship between these variables and PTSD. In this sense, current findings suggest that the presence of PTSD in subjects with first psychotic episodes is higher if 1) they have a previous history of trauma, 2) use dysfunctional assessment and coping strategies in front of stress (e.g., experience of uncontrollability), and 3) show comorbid depressive symptoms 4,[82][83][84][88][89][90] .…”
Section: -Theories Explaining the Association Between Ptsd And Psychosismentioning
confidence: 99%
“…On the other hand, within this unidirectional theory, a series of mainly cross-sectional studies have aimed at determining the risk of having PTSD as a result of psychosis onset, a fact called PP-PTSD 4 . On this issue, many studies with clinical samples of subjects with first psychotic episodes showed that the prevalence of PTSD ranges from 11% to 67%, being diagnosed in a third of patients assessed on average 4,[82][83][84][85][86][87][88] .…”
Section: -Theories Explaining the Association Between Ptsd And Psychosismentioning
confidence: 99%
See 2 more Smart Citations